Determination of Total Polyphenols and Nutritional Composition of Two Different Types of Ficus carica Leaves Cultivated in Saudi Arabia - Ghazi, Fatimah; Rahmat, Asmah; Yassin, Zaitun; Ramli, Nurul Shazini; Buslima, Nurul Amira (Pakistan Journal of Nutrition, 2012)
Ficus carica grows in tropical and subtropical regions of Saudi Arabia. The current study was conducted to evaluate the proximate analyses, minerals, alpha-tocopherol and vitamin C contents, and to investigate the antioxidant capacities of aqueous and methanolic extracts prepared from Ficus carica leaves. The antioxidant capacities in the forms of DPPH and FRAP were evaluated by spectrophotometric methods. Alpha-tocopherol and vitamin C contents were determined by using a high-performance liquid chromatography (HPLC)-UV method. Total phenolic content was determined by using the Folin-Ciocalteau method. The results indicated that TPC, DPPH and FRAP values were higher in methanolic extract of big Ficus carica leaf (412.37±57.9mg GAE/100 g, 63.29±2.51% and 131.39±13.96 mmol Fe2+/100 g) in comparison to small leaf. Total phenolics were however higher in aqueous extract compared to methanolic. The results clearly demonstrate that these extracts have antioxidant capacity though there was no significant correlation between total phenolic content and antioxidant activity. Also, nutritional composition of Ficus carica leaves showed that they are good sources of minerals. Ficus carica leaf is therefore a rich source of polyphenols and has high antioxidant properties.